Assessment of Microshear Bond Strength: Self-Etching Sealant versus Conventional Sealant. - Mina Biria; Amir Ghasemi; Hassan Torabzadeh; Arash Shisheeian; Alireza Akbarzadeh Baghban (Tehran University of Medical Sciences, 2014)
Recently, self-etching fissure sealants have been introduced to reduce technical sensitivity; however, their efficacy should be assessed. The aim of this study was to assess of the microshear bond strength of self-etching and conventional fissure sealants.Thirty non-carious third molars were randomly divided into three groups (N=10). Microcylinders of Concise fissure sealant were bonded to prepared buccal and lingual surfaces using the two following procedures. In the first group, phosphoric acid was used to prepare the substrate; whereas in group two, Concise was used in combination with Prompt L-Pop. In group 3, a self-etching fissure sealant (Enamel Loc) was utilized per se. After 24 hours, the samples were subjected to 500 rounds of thermocycling and shear bond testing using a microtensile tester machine with a crosshead speed of 0.5mm/min. Data were analyzed using one-way repeated measure ANOVA and Bonferroni Post HOC tests (SPSS version 16).THE MEAN AND STANDARD DEVIATION OF MICROSHEAR BOND STRENGTH OF THE GROUPS WERE AS FOLLOWS: Group 1: Concise+ etching (14.59 ± 1.19 MPa), Group 2: Concise+Prompt L-Pop (12.86 ± 1.98 MPa), and Group 3: Enamel Loc (5.59 ± 0.72 MPa). One-way ANOVA revealed that all the differences were significant and the conventional sealant exhibited the highest mean bond strength.Conventional sealant using phosphoric acid etch application prior to fissure sealant application demonstrated more bond strength in comparison with that of self-etch bonding and self-etch sealant.